Remote data access in computational jobs on the ATLAS data grid - Begy Volodimir (EPJ Web of Conferences, 2019)
This work describes the technique of remote data access from computational jobs on the ATLAS data grid. In comparison to traditional data movement and stage-in approaches it is well suited for data transfers which are asynchronous with respect to the job execution. Hence, it can be used for optimization of data access patterns based on various policies. In this study, remote data access is realized with the HTTP and WebDAV protocols, and is investigated in the context of intra- and inter-computing site data transfers. In both cases, the typical scenarios for application of remote data access are identified. The paper also presents an analysis of parameters influencing the data goodput between heterogeneous storage element - worker node pairs on the grid.